TAX LAW AND ITS IMPLICATIONS FOR PEOPLE'S WELFARE - Jaenudin Umar (International Journal Labs, 2024)
Taxes are a crucial instrument in determining a country's revenue. However, challenges remain, especially in the face of societal resistance to tax collection. To achieve people's welfare, tax regulations are needed, namely tax laws, which require public awareness. Therefore, this paper will discuss the effect of tax law on the welfare of the Indonesian people. This paper uses the type of data that produces descriptive evidence, collects information about the relationship between variables, and deepens the data used in the study in this paper. This study uses secondary documents in the form of writing and figures from articles and news with trusted sites as the object of discussion in this report. The results show that taxes play a central role in Indonesia's economy, and the main source of state revenue is the income sector. Tax amnesty can be a solution to increase tax revenue by capturing new taxes and increasing public awareness about the importance of adherence to tax laws. Increased public awareness is needed so that facilities, education, services, and security can be improved to achieve better public welfare.